Kadar Bioaktif dan Aktivitas Antioksidan Seduhan Kopi Arabika dengan Variasi Metode Penyeduhan - Christian Liguori; Puspo Edi Giriwono; Dian Herawati (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
Coffee contains abundant bioactive compounds related to health, among which are phenolic acids and diterpenes. This study aimed to investigate phenolic acids and diterpenes content in Arabica Gayo coffee, and its in-vitro antioxidant activities due to different brewing methods. The manual brewing methods used were tubruk (steeping), V60 drip, and hanging drip bag. The analysis conducted was determination of phenolic acid content as chlorogenic acid isomers (as 3-caffeoylquinic acid (3-CQA), 4-caffeoylquinic acid (4-CQA), and 5-caffeoylquinic acid (5-CQA)), diterpenes content (as cafestol and kahweol), and antioxidant activity using DPPH and FRAP method. The result showed that tubruk brew had 3-CQA, 4-CQA, and 5-CQA content of 0.38, 0.45, and 1.11 mg/mL, respectively, while V60 brew contained 0.39, 0.45, and 1.18 mg/mL, respectively. They were significantly higher than those in the drip bag, 0.25, 0.33, and 0.85 mg/mL, respectively. Cafestol and kahweol content in tubruk were significantly higher, reaching 3.03 and 7.86 mg/L consecutively, as in V60 were 0.40 and 1.02 mg/L and in drip bag were 0.46 and 0.85 mg/L. DPPH result displayed no significant difference per sample volume (918.45-921.17 mg ascorbic acid equivalent/L). FRAP result showed tubruk brew has the highest activity with 635.12 mg gallic acid equivalent/L, compared to V60 and drip bag brew at 560.91 and 551.10 mg gallic acid equivalent/L, consecutively. The results revealed that brewing methods affect the bioactive content of the final brew, in this research were phenolic acids and diterpenes. Various methods may differ in the variety and amount of other extracted bioactive compounds, so which affects the antioxidant activities of coffee brew.